Clinical Assessment of Ultrasound-Guided Local Lauromacrogol Injection Combined With Curettage and Hysteroscopy for Cesarean Scar Pregnancy - Wu, Qing; Liu, Xia; Zhu, Lin; Zhu, Yichen; Mei, Tingting; Cao, Shanshan; Shen, Yan; Ding, Jun; Lin, Tan (Frontiers in Pharmacology, 2020)
Background: To evaluate the efficacy, safeness and cost of ultrasound-guided local lauromacrogol injection (USG-LLI) combined with curettage and hysteroscopy for cesarean scar pregnancy (CSP). Methods: This was a retrospective study included 151 CSP patients diagnosed with CSP from June 2017 to December 2019, and treated by USG-LLI (n = 86) or uterine artery embolization (UAE) (n = 65) combined with curettage and hysteroscopy. Clinical data and outcome were analyzed. Results: There were no significant differences in basic clinical characteristics in the two groups. Two groups showed the similar success rates. USG-LLI group, compared with UAE group had significantly lower complication rates (9.30 vs. 44.62%), lower total costs (both medical and non-medication cost) (p < 0.05). Conclusions: USG-LLI combined with curettage and hysteroscopy is a feasible method to treat CSP with minimal invasion and high efficacy. Moreover, compared with curettage after UAE, USG-LLI exhibited lower complication rate and required fewer expenses.